Complete sequences of two new KPC-harbouring plasmids in Klebsiella pneumoniae ST11 strains in China. (March 2021) - Zhai, Yao; Li, Daixi; Du, Pengcheng; Zhang, Zhao; He, Zilong; Guo, Yatao; Chen, Yusheng; Kang, Yu; Hu, Songnian; Gao, Zhancheng
Highlights: Two novel bla KPC-2 -bearing plasmids were identified and sequenced. A novel type of bla KPC-2 genetic structure was identified. Spread of the plasmids was due to clonal dissemination of ST11 KPC-producing K. pneumoniae . Abstract: Objectives: Klebsiella pneumoniae carbapenemase (KPC) has spread across the world. The present study focused on exploring the sequences of two new KPC-harbouring plasmids in K. pneumoniae . Methods: Eighteen KPC-harbouring K. pneumoniae isolates were collected from a tertiary teaching hospital in 2014 in Fujian, China, among which two new KPC-harbouring plasmids (pF77 and pF5) we identified. The characteristics of the plasmids and the isolates carrying them were investigated in detail. Results: The two KPC-harbouring plasmids (pF5 and pF77) carried the antimicrobial resistance genes bla KPC-2, bla CTX-M-65, bla SHV-12, catA2 and fosA3 . Detailed sequence comparison revealed that the two plasmids might have evolved from recombination of the previously reported plasmids pKP1034 and pCT-KPC, which were considered to evolve from ancestor plasmids pHN7A8, pKPC-LK30 and pKPHS2. Plasmids pF5 and pF77 were non-conjugative and were mainly identified in sequence type 11 (ST11) K. pneumoniae isolates. Additionally, 4–55 core single nucleotide polymorphisms (SNPs) were identified in each pair of sequenced isolates that carried the identified plasmids. Conclusion: Plasmids pF5 and pF77 as well as the previously reported plasmids pKP1034 and pCT-KPC were all detected in 2013–2014 in South China and were carried by ST11 K. pneumoniae isolates. SNP analysis indicated high similarity of the sequenced isolates. Therefore, spread of the group of plasmids may be due to an outbreak of clonal dissemination of ST11 KPC-producing K. pneumoniae . This study also highlights the importance of plasmid analysis in the surveillance and control of antibiotic resistance spread in clinical isolates.